Compression of polystyrene and polypropylene foams for energy absorption applications: A combined mechanical and microstructural study. (January 2019) - Andena, Luca; Caimmi, Francesco; Leonardi, Lidia; Nacucchi, Michele; De Pascalis, Fabio
In many applications, polymeric foams (such as expanded polystyrene or expanded polypropylene) are used for protection from impacts. Standard design requires the foam to maximize the energy absorption, thus achieving large deformations (typically up to 25% and above in compression) while maintaining the stress level below a threshold value. In this work, steam chest-moulded EPS and EPP were characterized in relation to their density, microstructure and applied strain rate. Typical mechanical parameters (elastic moduli and plateau stress in compression) were compared with existing models and data in the literature. The strain-rate dependence was accurately described using Nagy's phenomenological model. The mechanical behaviour of the foams was then correlated with their microstructure, as investigated using scanning electron microscopy and X-ray micro-tomography. Structural parameters were obtained using both (2D and 3D) techniques and relevant results were compared.